Cardiovascular responses to NMDA injected into nuclei of hypothalamus or amygdala in conscious rats - AKICI, AHMET; ONAT, FİLİZ (KARGER, 2000)
The nuclei of hypothalamus and amygdala have been shown to be involved in the central cardiovascular homeostasis. Recent studies suggest that glutamate-containing neurons have an important role in the regulation of the central cardiovascular function. In this study, we demonstrate the roles of the central nucleus of the amygdala and the paraventricular nucleus of the amygdala and the paraventricular nucleus or the dorsomedial nucleus of the hypothalamus in N-methyl-D-aspartate (NMDA) induced blood pressure and heart rate changes in conscious Sprague-Dawley rats. Intracerebroventricular or parenchymal injections of NMDA evoke increases in arterial pressure. The NMDA-induced elevations in brood pressure are more prominent when NMDA is administered into the dorsomedial nucleus of the hypothalamus, Microinjections of NMDA into the dorsomedial hypothalamus exert significant heart rate increases, whereas NMDA when administered into the paraventricular nucleus of the hypothalamus or into the central nucleus of the amygdala has no significant effect on the heart rate. The dorsomedial nucleus of the hypothalamus is found to be the most effective site in this respect, The present study provides strong evidence for the tonic glutamatergic influence on blood pressure and heart rate via NMDA receptors located within the dorsomedial nucleus and to a lesser extent via those located within the paraventricular nucleus of the hypothalamus. Copyright(C) 2000 S. Karger AG, Basel.
Keywords: dorsomedial nucleus; paraventricular nucleus; N-methyl-D-aspartate; central cardiovascular regulation; microinjections; AMINO-ACID RECEPTORS; SPINAL-CORD; ANTAGONISTS; GLUTAMATE; EXCITOTOXICITY; INVOLVEMENT; TACHYCARDIA; INCREASES; SYSTEM; STRESS